Relationship between higher-standard neck circumference in women and risk factors of coronary artery disease - Nasrollah, S; Jalalmanesh, Sh; Mohammadzadeh, Sh; Mahmoodi, M (Advances in Nursing & Midwifery, 2008)
Introduction Coronary artery disease is the most common cardiovascular disorder with the highest rate of mortality, disability and costs. The prevalence of its risk factors is rapidly increasing worldwide. The Purpose of this descriptive correlative study was to determine the relationship between higher-standard neck circumference and some risk factors (hyperlipidemia, hypertension) in women with coronary artery disease in hospitals affiliated to Medical Universities of Tehran in 2006. Materials and Methods 199 women were selected by Poisson sampling method. Data were collected by an interview and documentation form in 2 parts: Demographics and clinical examination (blood pressure, neck circumference, body mass index). Results 84.4% of the subjects had higher-standard neck. This was significantly related to high blood cholesterol, LDL, HDL, triglyceride, systolic as well as diastolic pressures (P=0.05). A significant relationship was also found between higher-standard neck and some risk factors by controlling such personal factors as age, occupation, educational level, history of hyperlipidemia and hypertension, history of taking lipid- as well as blood-pressure reducing drugs, and duration of hyperlipidemia and hypertension (P=0.05). Conclusion With respect to the relationship between higher-standard neck and some risk factors in women with coronary artery disease, providing appropriate educational programs in this regard is suggested. Keywords: Higher-standard neck circumference, Hyperlipidemias, Hypertension.